Identifikasi Karakteristik Masjid Kuno Indonesia Pada Masjid Tuha Gunong Kleng Aceh Barat - Alfikhairina Jamil (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract. Mosques are works of Islamic architecture that are closest to our everyday life. Masjid Tuha Gunong Kleng is located in West Aceh, and is one of the mosques that can represent the development of ancient Indonesian mosque architecture from time to time. Visually, Masjid Tuha Gunong Kleng shows many similarities with other ancient mosques in Indonesia. Eventhough Masjid Tuha Gunong Kleng has been designated as a cultural heritage site by the Aceh Cultural Heritage Conservation Center, in-depth studies about Masjid Tuha Gunong Kleng is still difficult to get, both from either architectural or historical perspective. This research aims to identify the characteristics of ancient Indonesian mosques that can be found at Masjid Tuha Gunong Kleng. The implementation of this research also has the purpose to support and give contribution towards the efforts to preserve Masjid Tuha Gunong Kleng’s cultural heritage site. This research uses qualitative descriptive method and is exploratory in nature. Data collection techniques in this research were carried out using observation and interview methods. The results of this research shows that there are several characteristics of ancient Indonesian mosques that can be found in Masjid Tuha Gunong Kleng, namely the shape of the plan, foundation, roof, mihrab and porch. There are also several characteristics that are not relevant to Masjid Tuha Gunong Kleng, namely the fence dividing the mosque area, location, Qibla direction, and quality of mosque construction.